2004
DOI: 10.1242/jcs.01148
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of Pyk2 and Cbl to lipid rafts mediates signals important for actin reorganization in growing neurites

Abstract: Protein tyrosine kinase Pyk2 and multifunctional adaptor protein Cbl are implicated in the regulation of the cytoskeleton in several cell types. We report that Pyk2 and Cbl form a signaling complex that is translocated to lipid rafts and is enriched in growth cones of differentiating PC12 cells following growth factor stimulation. We found that Pyk2 and Cbl interacted with the adaptor protein ArgBP2, which also bound to flotillin-1, a component of lipid raft microdomains. These interactions contributed to recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 66 publications
1
86
0
1
Order By: Relevance
“…The intracellular localization of Pyk2 is regulated by different cellular conditions and by specific cytokines or integrin clustering (8,36,44,46,47). Our studies indicated that Pyk2 protein levels transiently decreased in OBs co-cultured with MKs (see Fig.…”
Section: Cytoskeletal Regulation Of Obs By Mks-mentioning
confidence: 63%
“…The intracellular localization of Pyk2 is regulated by different cellular conditions and by specific cytokines or integrin clustering (8,36,44,46,47). Our studies indicated that Pyk2 protein levels transiently decreased in OBs co-cultured with MKs (see Fig.…”
Section: Cytoskeletal Regulation Of Obs By Mks-mentioning
confidence: 63%
“…Flotillin proteins are expressed during retinal axon outgrowth and regeneration (Schulte et al, 1997), are involved in actin reorganization during neurite outgrowth (Haglund et al, 2004), and when expressed in Cos cells, induce the formation of a neuronal morphology (Hazarika et al, 1999). Because Xenopus is a particularly well-suited vertebrate in which to test the developmental function of novel genes, this description of the early and progressively restricted expression of flotillin1 before and during nervous system development provides important groundwork for future functional studies.…”
Section: Resultsmentioning
confidence: 99%
“…Second, the membrane interaction of c-Cbl-mediated by TKB is atypical, as it does not require an intact SH2-like domain of c-Cbl (Figure 3). The involvement of the proline-rich region of c-Cbl in its membrane association was not surprising, as many membrane-associated proteins contain SH3 domains and as this region has been shown to influence localization of c-Cbl to actin cytoskeleton in fibroblasts (Scaife and Langdon, 2000;Scaife et al, 2003a) and to lipid rafts in adipocytes and neurites Kimura et al, 2001;Haglund et al, 2004). However, the TKB domain of c-Cbl bound to the membrane in a phosphotyrosine-independent fashion, thus prompting us to search for proteins that could mediate this atypical binding.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of multiple interaction modules in c-Cbl underlies the versatility of its interactions and the influence of c-Cbl on a variety of biological processes (Schmidt and Dikic, 2005;Thien and Langdon, 2005;Swaminathan and Tsygankov, 2006). c-Cbl is both an E3 ubiquitin ligase involved in the negative regulation of protein tyrosine kinases (PTK) (Levkowitz et al, , 2000Miyake et al, 1999;Waterman et al, 1999;Rao et al, 2001;Yokouchi et al, 2001) and an adaptor protein involved in multiple biological phenomena, including cytoskeletal events (Tanaka et al, 1996;Ojaniemi et al, 1997;Meng and Lowell, 1998;Sanjay et al, 2001;Scaife et al, 2003a, b;Haglund et al, 2004). In several instances, tyrosine phosphorylation of c-Cbl has been shown to be crucial for c-Cbl-mediated adaptor effects (Ojaniemi et al, 1997;Feshchenko et al, 1999;Sanjay et al, 2001).…”
mentioning
confidence: 99%